Could TDE outflows produce the PeV neutrino events?. Issue 3 (14th June 2022) - Wu, Han-Ji; Mou, Guobin; Wang, Kai; Wang, Wei; Li, Zhuo
ABSTRACT: A tidal disruption event (TDE), AT2019dsg, was observed to be associated with a PeV neutrino event, IceCube-191001A, lagging the optical outburst by a half year. It is known that TDEs may generate ultra fast outflows. If the TDE occurs in a cloudy environment, the outflow-cloud interactions may form shock waves which generate accelerated protons and hence, delayed neutrinos from hadronic interactions in clouds. Here, we investigate the neutrino production in AT2019dsg by examining the TDE outflow-cloud interaction model. We find that, for an outflow with a velocity of 0.07 c and a kinetic luminosity of 10^45 erg s^-1, protons may be accelerated up to ∼60 PeV by the bow shocks, and generate PeV neutrinos by interactions with clouds. The predicted neutrino number in this model depends on the uncertainties of model parameters and in order to match the observations, some challenging values of parameters have been involved. The PeV neutrino event number can be ∼4 × 10 −3 for a hard proton index Γ = 1.5.